Industrial relations : a short history of ideas and learning - Elvander, Nils; Ekstedt, Eskil; Malmberg, Jonas (Stockholm: Arbetslivsinstitutet - National Institute for Working Life, 2002)
"Nils Elvander, Eskil Ekstedt, Jonas Malmberg... et al. DIGITAAL TE RAADPLEGEN IN DE LEESZAAL"